Analysis of human errors in nuclear power plant event reports - Meihui Zhang; Licao Dai; Wenming Chen; Ensheng Pang (Nuclear Engineering and Technology, 2025)
Human errors play a critical role in influencing the safety of nuclear power plants. This paper aims to better understand the impact of human errors on nuclear power plant operations by utilizing a modified Human Factors Analysis and Classification System (HFACS) model to analyze 190 Licensee Event Reports (LERs) from Chinese nuclear power plants, spanning the years 2007–2020. The analysis classifies errors into two categories: active errors and latent errors, followed by a detailed examination of each. The results reveal that 53 % of events involved active errors, while 92 % were associated with latent errors. A significant negative correlation was found between the number of latent error events and the operational age of the nuclear power plants, with latent error events decreasing as operational time increases. The first five years of a plant's operation were identified as a high-risk period for latent conditions, highlighting the importance of regular testing for early detection. Further, chi-square tests and odds ratio analysis identified the primary sequence of active errors and latent errors, which is as follows: Organizational Processes→Inadequate Supervision→ Environmental Factors→Skill-based Errors/Knowledge-based Errors. These findings emphasize that effective prevention and management of human errors, particularly latent errors, are crucial for enhancing the long-term safety and operational reliability of nuclear power plants.